Village Food Security Management Through Community Participation in Ngampelsari: Pengelolaan Keamanan Pangan Desa Melalui Partisipasi Masyarakat di Ngampelsari - Lestari, Fitriah Eka; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Food security is a key pillar of sustainable development in Indonesia, supported by national and village-level initiatives. Specific Background: Ngampelsari Village implemented food security programs funded by the Village Fund focusing on aquaculture, livestock, and hydroponic agriculture. Knowledge Gap: However, the program’s effectiveness and long-term sustainability have not been systematically evaluated. Aims: This study analyzes the effectiveness of food security implementation in achieving sustainable community welfare. Results: The findings reveal that while community participation and funding allocation were strong, program outcomes remained suboptimal due to limited technical capacity, poor infrastructure, and low production results. Novelty: The study offers a comprehensive evaluation model combining quantitative field data with qualitative stakeholder analysis to measure local food program performance. Implications: Strengthening technical training, infrastructure, and continuous monitoring is required to improve the effectiveness and sustainability of food security initiatives. Highlights: Program funded by Village Fund but limited in results. Human resource and infrastructure issues persist. Technical training and evaluation are needed.